Chronic ketamine reduces the peak frequency of gamma oscillations in mouse prefrontal cortex ex vivo - James M. McNally; Robert W. McCarley; Ritchie E. Brown (Frontiers in Psychiatry, 2013)
Abnormalities in EEG gamma band oscillations (GBO, 30-80 Hz) serve as a prominent biomarker of schizophrenia (Sz), associated with positive, negative and cognitive symptoms. Chronic, subanesthetic administration of antagonists of N-methyl-D-aspartate receptors (NMDAR), such as ketamine, elicits behavioral effects and alterations in cortical interneurons similar to those observed in Sz. However, the chronic effects of ketamine on neocortical GBO are poorly understood. Thus, here we examine the effects of chronic (5 daily i.p. injections) application of ketamine (5 and 30 mg/kg) and the more specific NMDAR antagonist, MK-801 (0.02, 0.5, and 2 mg/kg), on neocortical GBO ex vivo. Oscillations were generated by focal application of the glutamate receptor agonist, kainate, in coronal brain slices containing the prelimbic cortex. This region constitutes the rodent analogue of the human dorsolateral prefrontal cortex, a brain region strongly implicated in Sz-pathophysiology. Here we report the novel finding that chronic ketamine elicits a reduction in the peak oscillatory frequency of kainate-elicited oscillations (from 47 to 40 Hz at 30 mg/kg). Moreover, the power of GBO in the 40-50 Hz band was reduced. These findings are reminiscent of both the reduced resonance frequency and power of cortical oscillations observed in Sz clinical studies. Surprisingly, MK-801 had no significant effect, suggesting care is needed when equating Sz-like behavioral effects elicited by different NMDAR antagonists to alterations in GBO activity. We conclude that chronic ketamine in the mouse mimics GBO abnormalities observed in Sz patients. Use of this ex vivo slice model may be useful in testing therapeutic compounds which rescue these GBO abnormalities.